EVALUASI SISTEM INFORMASI RUMAH SAKIT DI RUMAH SAKIT BHAYANGKARA DENPASAR DENGAN MENGGUNAKAN FRAMEWORK COBIT 5 - Bagus Sayoga D. Mahadipha; I Nyoman Mahayasa Adiputra (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTBackground: The use of information systems in an agency, namely a hospital, certainly requires an internal control mechanism. Evaluation of an information system is important to measure the extent to which the implementation of the information system is currently running. Bhayangkara Hospital has never carried out an evaluation related to SIMRS so it is not known to what extent the achievements of SIMRS implementation are able to realize the goals and vision and mission of Bhayangkaya Hospital. Subjects and Methods: This research is a cross-sectional observational study, located at Rs. Bhayangkara Denpasar, population is HR at Rs. Bhayangkara totaled 191 people, purposive sampling technique was 25 samples, the research instrument was a COBIT 5 questionnaire, COBIT 5 data analysis used capability levels adapted from ISO/IEC 15504-2 and simple mathematical equations by the guidelines for calculating capability values. Results: Domain MEA 01 obtained a capability value of 2.25. MEA 02 domain obtained a capability value of 2.18. MEA 03 domain obtained a capability value of 2.20. The total value of the overall capability is 2.21 and is at level 2, namely manage process. Conclusion: The capability value obtained is Rs. Bhayangkara is still below the desired target of 4.51-5.00 optimizing process. SIMRS at Rs. Bhayangkara Denpasar has been running and has been managed (manage process) to be able to achieve the hospital's goals, but it has not been implemented with the right method and does not have the right boundaries.Keyword: Evaluation, SIMRS, COBIT 5, MEAABSTRAK Latar Belakang: Kontrol internal perlu dilakukan pada sistem informasi yang di implementasikan di sebuah rumah sakit. Evaluasi sistem informasi dilakukan untuk mengukur capaian penerapan sistem informasi yang sedang berjalan. Rumah sakit Bhayangkara tidak pernah melaksanakan evaluasi terkait dengan SIMRS sehingga belum diketahui sejauh mana capian implementasi SIMRS mampu merealisasikan tujuan serta visi dan misi dari rumah sakit Bhayangkaya. Subjek dan Metode: Penelitian merupakan penelitian observasional cross sectional, berlokasi di Rs. Bhayangkara Denpasar, populasi adalah SDM di Rs. Bhayangkara berjumlah 191 orang, teknik pengambilan sampel purposive sampling berjumlah 25 sample, instumen penelitian berupa kuisioner COBIT 5, analisis data COBIT 5 digunakan capability level yang diadopsi dari ISO/IEC 15504-2 dan persamaan matematika sederhana sesuai dengan pedoman penghitungan nilai kapability. Hasil: Domain MEA 01 memperoleh nilai kapability sebesar 2,25. Domain MEA 02 memperoleh nilai kapabilty sebesar 2,18. Domain MEA 03 memperoleh nilai kapability sebesar 2,20. Total nilai kapability keseluruhan adalah 2,21 dan beradda pada level 2 yaitu manage process. Kesimpulan: Nilai kapability yang diperoleh Rs. Bhayangkara masih dibawah target yang diinginkan yaitu 4,51-5,00 optimising process. SIMRS di Rs. Bahayangkar Denpasar sudah berjalan dan telah dikelola (manage process) untuk dapat mencapai tujuan rumah sakit namum belum diimplementasikan dengan metode yang tepat serta belum memiliki batasan-batasan yang tepat.Kata Kunci: Evaluasi, SIMRS, COBIT 5, MEA